2007
DOI: 10.1016/j.geoforum.2007.03.012
|View full text |Cite
|
Sign up to set email alerts
|

NIMBY localism and national inequitable exclusion alliances: The case of syringe exchange programs in the United States

Abstract: Syringe exchange programs (SEPs) aim to reduce the harm associated with injection drug use (IDU). Although they have been accepted as critical components of HIV prevention in many parts of the world, they are often unwelcome and difficult to set up and maintain, even in communities hardest hit by IDU-related HIV transmission. This research examines socio-cultural and political processes that shape community and institutional resistance toward establishing and maintaining SEPs. These processes are configured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 50 publications
3
69
0
1
Order By: Relevance
“…Though concerns that SEPs increase crime rates and exposure to discarded syringes are unfounded, 76,77 the location of SEP sites remains controversial. [2][3][4] Our results support past research that has found that the presence of an SEP in a geographic area reduces HIV risk behavior among local residents who inject; 24-26 moreover, we find that this benefit extends to injecting residents who do not personally go to the SEP site.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Though concerns that SEPs increase crime rates and exposure to discarded syringes are unfounded, 76,77 the location of SEP sites remains controversial. [2][3][4] Our results support past research that has found that the presence of an SEP in a geographic area reduces HIV risk behavior among local residents who inject; 24-26 moreover, we find that this benefit extends to injecting residents who do not personally go to the SEP site.…”
Section: Discussionsupporting
confidence: 89%
“…[2][3][4] Local business leaders and residents, for example, have protested the establishment and ongoing operation of SEPs in their midst. 3 The 2010 appropriations law that lifted the federal ban codified this controversy: the law stipulates that, to be eligible for federal funding, SEPs must first receive local police department and public health department approval on the location of their sites. 1 This paper is thus designed to further inform ongoing debates about spatial access to SEPs.…”
mentioning
confidence: 99%
“…This conclusion echoes past work that has found that the spatial distribution of harm reduction sites and services is largely shaped by sociopolitical processes. 63,84,85 Our analyses thus suggest that ESAP access is a racialized feature of the risk environment in NYC health districts; that is, it appears to be a protective feature that is distributed across geographic areas according to local racial/ethnic composition. This distribution may have several implications.…”
Section: Discussionmentioning
confidence: 75%
“…Drawing on research on health services geography, [59][60][61] we define "spatial access to ESAP pharmacies" as a property of each health district that reflects the local availability of pharmacies enrolled in the ESAP program in a given year. This construct is distinct from "aspatial access," which refers to barriers and facilitators of healthcare access that are not rooted in geography (e.g., stigma 62,63 ). 61,64 We also focus on potential spatial access to ESAP pharmacies, which concerns reasonable possible use, rather than revealed (or actual) service use.…”
Section: Methodsmentioning
confidence: 99%
“…Private and publicly funded residential placements often resemble imprisonment, especially when they are mandates, coerced, and take place in settings called "level 14 group homes" in which secure confinement mechanisms rival the most technologically equipped prisons and detention centers (Cox, 2011). Practices of surveillance, banishments, and NIMBYisms are all part of the carceral project, even if their research settings are far removed (or not so far in many cases) from the prison (Beckett and Herbert, 2010;Hubbard, 2004Hubbard, , 2005Tempalski et al, 2007;Walby, 2005). For many, incarceration does not end at the prison, but rather follows them "into the community" and through life (Travis, 2002).…”
Section: Introductionmentioning
confidence: 99%